2005
DOI: 10.1086/426396
|View full text |Cite
|
Sign up to set email alerts
|

Suppression and Modulation of Cellular and Humoral Immune Responses toHaemophilus influenzaeType B (Hib) Conjugate Vaccine in Hib–Diphtheria‐Tetanus Toxoids–Acellular Pertussis Combination Vaccines: A Study in a Rat Model

Abstract: We assessed a rat model to evaluate the immunogenicity of Haemophilus influenzae type b (Hib) conjugate vaccines and the effect on Hib immunogenicity of combining 2 Hib vaccines (Hib-tetanus toxoid [TT]-A and Hib-TT-B) with diphtheria-TT-acellular pertussis (DTaP)(3) or DTaP(5)/inactivated poliovirus (IPV) vaccines. Rats were immunized subcutaneously with Hib alone or with Hib and DTaP-based vaccines; anti-Hib capsular polysaccharide IgG, poly-ribosyl-ribitol-phosphate (PRP), IgG subclass, and cellular immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Although tested, in some cases, up to nine years after their manufacture (and six years past their licensed expiry dates), vaccines were found to be of high quality throughout the period of manufacture (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) for Hib-TT A and 1996 to 2003 for Hib-TT B), judging by low levels of endotoxin and percent free saccharide, a measure of integrity, and were consistent with their product license specifications. In a rat model of immunogenicity which has demonstrated good correlation with human data, 16,19 there were also no significant differences observed between the tested vaccines received between 1996 and 2004, although the older batches were tested several years past the expiry of their designated shelf-life. Levels of total saccharide were steady throughout the period, based on the manufacturers' data at time of release, and retrospective analysis at NIBSC.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although tested, in some cases, up to nine years after their manufacture (and six years past their licensed expiry dates), vaccines were found to be of high quality throughout the period of manufacture (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) for Hib-TT A and 1996 to 2003 for Hib-TT B), judging by low levels of endotoxin and percent free saccharide, a measure of integrity, and were consistent with their product license specifications. In a rat model of immunogenicity which has demonstrated good correlation with human data, 16,19 there were also no significant differences observed between the tested vaccines received between 1996 and 2004, although the older batches were tested several years past the expiry of their designated shelf-life. Levels of total saccharide were steady throughout the period, based on the manufacturers' data at time of release, and retrospective analysis at NIBSC.…”
Section: Discussionmentioning
confidence: 94%
“…Several batches tested for quality were selected at random, one from each year, for immunogenicity testing, using a rat model which has shown good correlation with the human response. 16,19 All eight batches of Hib-TT A and seven of Hib-TT B induced substantial levels of anti-PRP antibodies, with no clear trend of any changes in the level of anti-PRP antibody response induced by the two vaccines with time ( Fig. 6).…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 96%
See 1 more Smart Citation
“…It has been shown that several factors may affect immune responses to this type of antigen, including the nature of the specific protein carrier for the Hib polysaccharide, the nature of the aluminum salt adjuvant added to the Hib antigen, the specific formulation characteristics of the combination vaccine, the ethno-ecological status of the vaccinees, and the primary series schedule. [18][19][20][21] It is clear that the variability of the anti-PRP responses in combination vaccines made of DTaPHib that is observed in randomized controlled trials of DTaP-Hib has been a major cause of licensure delays or even non-licensure by some regulatory authorities. This has been the case for DTaP 2Fr -Hib in some countries.…”
Section: Vaccine Formulation Effectmentioning
confidence: 99%
“…Some authors note that mice and rats provide a useful small-animal model for the study of influenza virus pathogenesis (15)(16)(17)(18)(19). Although the mouse is a commonly used preclinical model for studying the immunogenicity of influenza vaccines by using the same vaccine dose and administration routes as in humans (1), the response in rats is less variable among individual animals, making this animal the most suitable model in immunogenicity studies (20).…”
Section: Introductionmentioning
confidence: 99%